Control of Raw Material Inventory at Cireng and Cimol Nella Businesses Using EOQ Method (Economic Order Quantity) - Susanto, Resi Juariah (STIE Ekuitas, 2022)
This research is research in the field of culinary business where raw materials if stored for too long can cause damage as well as losses to the business owner. The businesses chosen were those of Cireng and Cimol Nella which had problems in supplying raw materials, namely flour. This research also aims to enable business actors to carry out an inventory of raw materials so that product quality is better maintained so that it does not change the taste of the product and the condition of the product is even better. From the existing problems, the method used is to use the application of the EOQ (Economic Order Quantity) formula because using this method is considered appropriate for calculating the number of times the right order is made in 1 month. Then the determination of the reorder point was made by the company when the stock of tapioca flour in the company was 77.87 kg. Economic Order Quantity, Safety Stock and Reorder Point are interrelated things to be able to find out the most optimal order quantity. Advice for business owners to always take into account when placing an order so that raw materials do not become wasteful or wasted due to damage.